2020
DOI: 10.1111/asj.13492
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of reproductive and growth performance of pigs on commercial swine farms in southern Kyushu, Japan

Abstract: The objective of the present study was to assess the productivity of pigs to investigate the time‐dependent change in productivity and compare productivity according to breeding company group and porcine reproductive and respiratory syndrome (PRRS) status on commercial swine farms in southern Kyushu, Japan. Data used in the present study were 245 annual productivity records from 2014 to 2018 obtained from 72 farms. Average sow inventory was 481.2 sows. Mean numbers of pigs weaned per sow per year and market pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The rate of increase in the PBA in this study doubled compared with that of the previous decade (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013), although different study designs are difficult to compare. Sasaki et al [26] found that the mean PBA increased by 0.20 annually from 11.1 in 2014 to 11.9 in 2018, which was similar to our results.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The rate of increase in the PBA in this study doubled compared with that of the previous decade (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013), although different study designs are difficult to compare. Sasaki et al [26] found that the mean PBA increased by 0.20 annually from 11.1 in 2014 to 11.9 in 2018, which was similar to our results.…”
Section: Discussionsupporting
confidence: 92%
“…The rapid increase in PBA during the study period was likely due to the introduction of highly prolific sows from the EU, which began around 2008 [28]. Previous studies in Japan [10,26] found that farms that introduced highly prolific sows from foreign companies had higher PBAs than did farms from domestic companies. A study from the Netherlands reported that the PWMFY increased by approximately 35% in the 20 years prior to 2009 owing to genetic selection and management techniques [11].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…With the rise of modern intelligent agriculture, how to grasp the growth status of pigs more efficiently and accurately has become a hot issue in the development of farming industry [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the recent worldwide increase in the prolificacy potential of sows due to genetic improvements (Hernández et al, 2018; Sasaki, Kawabata, et al, 2020), the number of piglets per litter is increasingly exceeding the number of functional teats. Such litters show an increase in preweaning mortality and variation of weaning weight within the litter (Quesnel, 2011; Theil et al, 2006).…”
Section: Introductionmentioning
confidence: 99%